Optimal Load Scheduling of Power Plants in a Grid Considering the Plant’s Capacity and Line Losses - Obi, P. I.; Oputa, O.; Amako, E. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
In a grid or part of a grid operated by a single service provider with various types of power plants, the total load demand on the grid can be serviced by the plants’ outputs in such a way that a minimum cost of energy is spent to generate this total demanded load thereby maximizing profit for the service providers without placing exorbitant tariff on customers. This paper considered how this can be archived in the Niger-Delta region of Nigeria (as a case study). We assumed that the power generated by the plants in the region is also consumed by the region. Using the Lagrnge multiplier optimization method in our analysis and for a total power demand/generation of , a total of  of fuel will be burnt. But with the system of running cost minimization developed in this paper, only about  of fuel was burnt in generating that same quantity of power demanded resulting in a net savings of . This is equivalent to ; with energy sold at ₦48/kWh in Nigeria, a total of ninety-eight thousand, seven hundred and thirty-six Naira (₦98,736.00) only will be saved each hour resulting in a net savings of eight hundred and sixty-four million, nine hundred and twenty-seven thousand, three hundred and sixty naira (₦864,927,360.00) only per annum. This is, therefore, recommended for implementation in running Nigeria’s power system.